2014
DOI: 10.5835/jecm.omu.31.02.007
|View full text |Cite
|
Sign up to set email alerts
|

The impact of omega-3 fatty acids on lung histopathology in mice model of chronic asthma

Abstract: Article History

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Bargut et al’s 12 study demonstrated a significantly reduced eosinophilic response in the OVA-exposed fish oil group when compared to the OVA-exposed control group. Eliaçik et al’s 14 study showed no significant difference in eosinophil concentration ratios between groups. Schuster et al’s 11 study showed that DHA, alone, produced significantly higher levels of bronchoalveolar lavage fluid (BALF) eosinophils than all other groups (p < 0.001), but did not show a significant difference in eosinophil levels between the control and the other n-3 PUFA groups.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Bargut et al’s 12 study demonstrated a significantly reduced eosinophilic response in the OVA-exposed fish oil group when compared to the OVA-exposed control group. Eliaçik et al’s 14 study showed no significant difference in eosinophil concentration ratios between groups. Schuster et al’s 11 study showed that DHA, alone, produced significantly higher levels of bronchoalveolar lavage fluid (BALF) eosinophils than all other groups (p < 0.001), but did not show a significant difference in eosinophil levels between the control and the other n-3 PUFA groups.…”
Section: Resultsmentioning
confidence: 89%
“… 12 Miranda et al’s 10 rat model demonstrated a significant increase in static lung compliance in fish-oil supplemented, asthmatic rats (p < 0.05); however, there was no significant variation between the post-exposure groups in pulmonary smooth muscle force of contraction or smooth muscle layer thickness. Eliaçik et al’s 14 model found that basement membrane thickness was significantly lowered after fish oil supplementation (p = 0.038), but found no significant difference in goblet cell numbers or subepithelial smooth muscle thickness of airways between the groups. On comparing lung airway resistance, Schuster et al’s 11 study of varying formulations of EPA and DHA in mice showed that the sole-DHA diet produced significantly higher resistance measurements than all other groups.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…33 Araşidonik asit (AA), inflamasyon ve bağışıklık düzenlenmesinde önemli rollere sahip olan prostaglandin (PG)'ler, lökotrien (LT)'ler ve ilgili bileşiklerin ön maddesidir. 34 Omega 6 (n-6)'nın zengin kaynakları mısırözü yağı, zeytinyağı, aspur yağı, fındık yağı, ayçiçek yağı, pamuk yağı ve soya yağı-dır. 13 İnflamasyonu düzenleyen lipit mediyatörleri-nin çoğu n-6 ya da n-3 yağ asitlerinden elde edilmektedir.…”
Section: Di̇yeti̇n Yağ İçeri̇ği̇unclassified